Theologie: Een dwaze wetenschap? - Marcel, Sarot (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
In the Netherlands, theology is currently disappearing from the non-confessional universities. That is to be deplored, since theology has several important public functions. One of these is that theology contributes to the ‘normative capital’ of a society. But is theology up to its public functions? Or has it become a pastime for an in-crowd that is irrelevant for the wider society? The argument proceeds in two stages. First: Can one adhere to the maxim Lex orandi, lex credendi without giving up one’s intellectual autonomy and becoming irrelevant to non-believers? By explaining this maxim in light of its origin with Prosper of Aquitaine, the author shows that this is indeed possible. Second: Is there something to be learnt from Erasmus of Rotterdam, who – while being a confessional theologian – has become an icon of modernity? The author argues on the basis of his Enchiridion and his Praise of Folly that Erasmus was a constructive theologian with serious attention for the spiritual life. We can learn from him (1) to uphold the highest academic standards, (2) to combine loyalty to confession with a critical attitude towards abuses, (3) to denounce abuses without attacking individuals, and (4) to root our theologies in the piety of a community.